Eksistensi Perbankan Syariah pada Lembaga Berbasis Agama Islam di Ponorogo - Anggraini, Yulia; Hidayatul Ummah, Restu Yulia; Suryaningsih, Ruliq (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This study aims to determine the existence of Islamic banking in Islamic-based institutions in Ponorogo. The development of the Islamic economy itself cannot be separated from the presence of Islamic banks in Indonesia. To support Islamic economic growth, of course this Islamic-based institution must also play an active role in driving Islamic economic growth by starting to transact in Islam. By supporting this growth Islamic institutions should also participate in using Islamic banking in financial transactions. However, from a sample of four Islamic based institutions, the results show that the four institutions are still using conventional banking for financial transactions. The results of this study found that the factors of authority and bureaucracy are still complicated and full of regulations, profit sharing or commonly called interest for conventional banking, CSR (Corporate Social Responsibility) funds, technology and facilities are factors that influence why religious-based institutions Islam has not used Islamic banking to conduct financial transactions